Treatment Strategy for Frozen Shoulder - Cho, Chul-Hyun; Bae, Ki-Choer; Kim, Du-Han (Clinics in orthopedic surgery, 2019)
Frozen shoulder (FS) is a common shoulder disorder characterized by a gradual increase of pain of spontaneous onset and limitation in range of motion of the glenohumeral joint. The pathophysiology of FS is relatively well understood as a pathological process of synovial inflammation followed by capsular fibrosis, but the cause of FS is still unknown. Treatment modalities for FS include medication, local steroid injection, physiotherapy, hydrodistension, manipulation under anesthesia, arthroscopic capsular release, and open capsular release. Conservative management leads to improvement in most cases. Failure to obtain symptomatic improvement and continued functional disability after 3 to 6 months of conservative treatment are general indications for surgical management. However, there is no consensus as to the most efficacious treatments for this condition. In this review article, we provide an overview of current treatment methods for FS.